2002
DOI: 10.1144/gsl.mem.2002.021.01.09
|View full text |Cite
|
Sign up to set email alerts
|

Pyroclastic flows and surges generated by the 25 June 1997 dome collapse, Soufrière Hills Volcano, Montserrat

Abstract: On 25 June 1997, an unsteady, retrogressive, partial collapse of the lava dome at Soufrière Hills Volcano lasted 25 minutes and generated a major pulsatory block-and-ash flow, associated pyroclastic surges and a surge-derived pyroclastic flow that inundated an area of 4 km2 on the north and NE flanks of the volcano. Three main pulses are estimated to have involved 0.78, 2.36 and 2.36 x 106m3 of debris and the average velocities of the fronts of the related block-and-ash flow pulses were calculated to be 15 ms-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
76
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 27 publications
5
76
0
Order By: Relevance
“…Ashcloud surges have also been known to overspill narrow channels, especially around valley bends, as at Merapi (Bourdier & Abdurachman 2001;Charbonnier & Gertisser 2008Lube et al 2011;Charbonnier et al 2013;Jenkins et al 2013;Komorowski et al 2013), Unzen (Yamamoto et al 1993;Fujii & Nakada 1999) and SHV (Loughlin et al 2002b). For the 25 June 1997 SHV BAF described in detail by Loughlin et al (2002b), detachment of ash-cloud surges was found to occur at valley bends and constrictions, and was related to the slope of the channel, and was enhanced by depositional filling. Cole et al (2002), analysing data collated from 14 SHV flows, found Komorowski et al (2010).…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Ashcloud surges have also been known to overspill narrow channels, especially around valley bends, as at Merapi (Bourdier & Abdurachman 2001;Charbonnier & Gertisser 2008Lube et al 2011;Charbonnier et al 2013;Jenkins et al 2013;Komorowski et al 2013), Unzen (Yamamoto et al 1993;Fujii & Nakada 1999) and SHV (Loughlin et al 2002b). For the 25 June 1997 SHV BAF described in detail by Loughlin et al (2002b), detachment of ash-cloud surges was found to occur at valley bends and constrictions, and was related to the slope of the channel, and was enhanced by depositional filling. Cole et al (2002), analysing data collated from 14 SHV flows, found Komorowski et al (2010).…”
Section: Previous Workmentioning
confidence: 99%
“…Surges may separate from valley-confined flows when steep topography or barriers are encountered, as was (Charbonnier & Gertisser 2011;Lube et al 2011;Charbonnier et al 2013;Jenkins et al 2013;Komorowski et al 2013). Ashcloud surges have also been known to overspill narrow channels, especially around valley bends, as at Merapi (Bourdier & Abdurachman 2001;Charbonnier & Gertisser 2008Lube et al 2011;Charbonnier et al 2013;Jenkins et al 2013;Komorowski et al 2013), Unzen (Yamamoto et al 1993;Fujii & Nakada 1999) and SHV (Loughlin et al 2002b). For the 25 June 1997 SHV BAF described in detail by Loughlin et al (2002b), detachment of ash-cloud surges was found to occur at valley bends and constrictions, and was related to the slope of the channel, and was enhanced by depositional filling.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Deposit volumes are typically in the order of 10 4 -10 6 m 3 for small to medium-sized (1-3 km run out) pyroclastic flows (Calder et al, 1999;Cole et al, 2002). Large dome collapses, in excess of 1 x 10 6 m 3 , have occurred on 47 occasions throughout the eruption to date (Calder and Bernstein, 2007).…”
Section: Lava Dome Growth Rockfalls and Seismicitymentioning
confidence: 99%
“…Furthermore variations in amplitude can occur as a result of the pulselike nature of flow generation, due to retrogressive collapse initiation (Loughlin et al, 2002), but also as a result of the pyroclastic flows changing proximity to the geophones as they approach and subsequently pass-by the stations (Jolly et al, 2002). Some pyroclastic flows, and most rockfalls, are only observed seismically and thus the seismic data, irrespective of its complexities, provides one of the most important and complete records for the collapse history of the dome.…”
Section: Lava Dome Growth Rockfalls and Seismicitymentioning
confidence: 99%